Association of Inpatient Antimicrobial Utilization Measures with Antimicrobial Stewardship Activities and Facility Characteristics of Veterans Affairs Medical Centers. Issue 5 (1st May 2017) - Graber, Christopher J.; Jones, Makoto M.; Chou, Ann F.; Zhang, Yue; Goetz, Matthew Bidwell; Madaras‐Kelly, Karl; Samore, Matthew H.; Glassman, Peter A.
Abstract : BACKGROUND: Antimicrobial stewardship programs (ASPs) have been advocated to improve antimicrobial utilization, but program implementation is variable. OBJECTIVE: To determine associations between ASPs and facility characteristics, and inpatient antimicrobial utilization measures in the Veterans Affairs (VA) system in 2012. DESIGN: In 2012, VA administered a survey on antimicrobial stewardship practices to designated ASP contacts at VA acute care hospitals. From the survey, we identified 34 variables across 3 domains (evidence, organizational context, and facilitation) that were assessed using multivariable least absolute shrinkage and selection operator regression against 4 antimicrobial utilization measures from 2012: aggregate acute care antimicrobial use, antimicrobial use in patients with non‐infectious primary discharge diagnoses, missed opportunities to convert from parenteral to oral antimicrobial therapy, and double anaerobic coverage. SETTING: All 130 VA facilities with acute care services. RESULTS: Variables associated with at least 3 favorable changes in antimicrobial utilization included presence of postgraduate physician/pharmacy training programs, number of antimicrobial‐specific order sets, frequency of systematic de‐escalation review, presence of pharmacists and/or infectious diseases (ID) attendings on acute care ward teams, and formal ID training of the lead ASP pharmacist. Variables associated with 2 unfavorable measures included bed size, the level of engagement with VA Antimicrobial Stewardship Task Force online resources, and utilization of antimicrobial stop orders. CONCLUSIONS: Formalization of ASP processes and presence of pharmacy and ID expertise are associated with favorable utilization. Systematic de‐escalation review and order set establishment may be high‐yield interventions.